2017
DOI: 10.1038/s41598-017-15569-1
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic dendritic cells are efficiently generated using minocycline and dexamethasone

Abstract: Tolerogenic dendritic cells (tDCs) represent a promising tool for cellular therapy against autoimmune diseases, allergies, and transplantation rejection. Numerous pharmacological agents are known to induce tDC generation. Minocycline, which has long been used as a broad-spectrum antibiotic, was recently shown to significantly increase the generation of DCs with regulatory properties. Here, we examined the effect of the combination of minocycline with dexamethasone, rapamycin, vitamin D3, and interleukin (IL)-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 48 publications
(46 reference statements)
2
38
0
1
Order By: Relevance
“… 33 Although we observed no difference in IL-10 production within 24 hours after LPS activation, the difference between mature cells and TolDCs was clear after 48 hours, indicating the tolerogenic potential of these cells. Lee et al 34 compared the effect of different stimuli (rapamycin, vitamin D3, IL-10, dexamethasone and minocycline) on DC generation with regulatory properties and observed that the level of IL-10 produced varies according to the stimulus. Further work shows that the culture time of these cells also influences the level of IL-10 produced.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Although we observed no difference in IL-10 production within 24 hours after LPS activation, the difference between mature cells and TolDCs was clear after 48 hours, indicating the tolerogenic potential of these cells. Lee et al 34 compared the effect of different stimuli (rapamycin, vitamin D3, IL-10, dexamethasone and minocycline) on DC generation with regulatory properties and observed that the level of IL-10 produced varies according to the stimulus. Further work shows that the culture time of these cells also influences the level of IL-10 produced.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dexamethasone as an agent for the induction of tolerogenic profile in DCs has been previously shown in both mouse bone marrow cells and from human monocytes (32-34). Tolerogenic dendritic cells derived by the use of pharmacological agents, such as dexamethasone alone or in combination, and subsequently induced maturation with LPS has previously been shown to acquire stable semi-mature and tolerogenic phenotype (35)(36)(37)(38). Furthermore, the use of LPS to generate tolerogenic dendritic cells has proved to be important to favor the regulatory and migratory capacity of these cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Схожие результаты были получены J.-H. Le с соавт., которые в ýкспериментальных моделях показали, что различные толерогенные стимулы, в том числе и дексаметазон, приводят к увеличению количества CD86 − B7-H1 + среди DC, индуцированных IL-4 [20].…”
Section: Discussionunclassified